2019
DOI: 10.1002/aoc.5063
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Electrochemical Studies of Anchored Chromium (III) Complex on Reduced Graphene Oxide via Diazonium Chemistry

Abstract: Covalently anchored chromium complex on reduced graphene oxide (rGO‐Cr) is successfully synthesised through trimethoxy silyl propanamine (TMSPA) and phenyl azo salicylaldehyde (PAS) coupling. The rGO‐Cr is characterised by Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), electron dispersive analysis of X‐rays (EDAX), Raman spectroscopy, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). Absorption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 91 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…The absorption and emission properties were screened to understand the switching nature of the molecule for a solution of 3024.3 M À 1 cm À 1 extinction coefficient. [27] Absorption and emission spectra of 1od are given in Figure 1(a) and (b). Table 1 illustrates the correlation between experimental and theoretical absorbance and emission spectra with their transitions.…”
Section: Uv-visible and Fluorescence Spectral Analysismentioning
confidence: 99%
“…The absorption and emission properties were screened to understand the switching nature of the molecule for a solution of 3024.3 M À 1 cm À 1 extinction coefficient. [27] Absorption and emission spectra of 1od are given in Figure 1(a) and (b). Table 1 illustrates the correlation between experimental and theoretical absorbance and emission spectra with their transitions.…”
Section: Uv-visible and Fluorescence Spectral Analysismentioning
confidence: 99%
“…[50] Jose et al synthesized covalently anchored azo derivatives, which showed photoswitching property. [84] Finally, due to the disruption of the π-conjugated structure during the covalent reaction, the water solubility of hybrid materials generated using the covalent technique is reduced. While the process has advantages in terms of grafting density and half-lifetime, it is a viable way to create photo-switching-based energy materials.…”
Section: Covalent Interactionsmentioning
confidence: 99%
“…Jose et al . synthesized covalently anchored azo derivatives, which showed photoswitching property [84] . Finally, due to the disruption of the π‐conjugated structure during the covalent reaction, the water solubility of hybrid materials generated using the covalent technique is reduced.…”
Section: Types Of Interactions Between the Template And Azobenzenementioning
confidence: 99%
“…Graphene oxide (GO) has received much attention among carbon nanomaterials due to its high mechanical strength, thermal, and electrical conductivity 2 . Besides, the carboxyl, hydroxy, and epoxy groups create GO as a desirable platform for further functionalizing molecules 3 , 4 . Other than functionalization approaches of GO, heteroatom doping is also important since it modifies the properties of GO extensively.…”
Section: Introductionmentioning
confidence: 99%